Association of stress and inflammatory diseases with serum ferritin and iron concentrations in neonatal calves - Sickinger, Marlene; Jörling, Jessica; Büttner, Kathrin; Roth, Joachim; Wehrend, Axel; Justus Liebig University Giessen (My University, 2025)
This study investigated the effects of iron supplementation and inflammatory disease on cortisol, white blood cell (WBC) count, total protein (TP), lactate, interleukin 1 β (IL1β), interleukin 6 (IL6), substance P (SP), hepcidin, haptoglobin, and ferric-reducing ability of plasma (FRAP) in calves. Correlation analyses for the aforementioned parameters with serum iron and ferritin were performed in 40 neonatal calves over the first 10 days of life. Neither iron supplementation, disease status, nor sex had statistically significant effects on the areas under the curve of ferritin, WBC, TP, IL1β, IL6, SP, hepcidin, haptoglobin, or FRAP. However, cortisol concentrations were influenced by disease development. Cortisol concentrations were higher at birth (44.1 ± 1.95 ng/mL) than on day 2 (38.8 ± 1.87 ng/mL) (p = 0.0477), and healthy animals exhibited lower cortisol concentrations than diseased calves (p = 0.0028). Correlation analyses indicated weak positive correlations between ferritin and IL1β (p = 0.0015; ρ = 0.49) and IL6 (p = 0.0011; ρ = 0.50), respectively. The clinical significance of these findings and resulting therapeutic consequences, especially with respect to iron supplementation, should be further investigated in calves and adult cattle.
Keywords: ddc:630